Peningkatan Literasi Bahasa dan Komputasi Siswa SMP Negeri 24 Kota Medan (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2025)
The low literacy and computational skills of class X students were detected from frequent language errors in communication. This often becomes a problem in literacy in the language aspect, especially for class X junior high school students, due to the many determinations between students' language needs and language skills. This is why community service is carried out to improve students' language and computational literacy skills in language. Language considerations can be used as an important element in smooth communication. The skills that are the focus are always related to the ability to listen, speak, read, write, count, and solve problems at the specific level needed according to the topic being discussed. This community service was carried out at SMP Negeri 24 Medan City for approximately one month. The approach taken was through socialization and training of language and computational literacy for students. The goal is to provide an understanding of the importance of language literacy skills in everyday life. The results of this community service show that these language skills, termed literacy skills, can improve students' understanding so that they can be developed in various fields of study. However, in a simpler context, literacy must be developed in a smaller scope, but have a significant impact.